Does changed referral options affect the use of MRI for patients with low back pain? Evidence from a natural experiment using nationwide data. Issue 6 (27th June 2019) - Jensen, Morten Sall; Olsen, Kim Rose; Morsø, Lars; Søndergaard, Jens; Schiøttz-Christensen, Berit
Abstract : Objectives: This study reports lumbar MRI referral patterns in the Region of Southern Denmark (RSD) and investigates the hypothesis that we will see an increase in imaging rates (MRI rates) following new referral options to lumbar MRI in the RSD in comparison with the other regions in Denmark from 2010 to 2013. Design: A difference-in-difference (DD) analysis, using general practitioners (GPs) in other regions as control, was used to test if the new referral options had an effect on the MRI rates. Setting: In 2010, RSD introduced organisational changes affecting the referral options for lumbar MRI. First, the possibility for direct referral to lumbar MRI was introduced GPs, and second, the region gathered all local spine departments into one specialist hospital called the Spine Centre. Participants: We retrieved all lumbar MRIs performed on patients aged 18+ performed on Danish hospitals from 2008 to 2013 using the registries from Statistics Denmark. We use sociodemographic information from all Danish citizens aged 18+ aggregated to GP level. Primary and secondary outcome measures: lumbar MRI scans per 1000 capita enlisted with a GP (MRI rates) were calculated based on GPs patient list. Four referral types were made to describe changes in referral patterns. Results: In total 183 389 patients received 240 760 lumbar MRIs in the period. The use of the direct referral option by GPs in the RSD increased by 115% in the period from 2010 to 2013 and accounted for 34% of all referrals (n=6545) in 2013. MRI rates were significantly higher in RSD following the organisational changes (DD 1.389(0.925–1.852) lumbar MRI per 1.000 enlisted with a GP). Conclusions: Introduction of organisational changes in RSD as direct referral to lumbar MRI from GPs and chiropractors as well as establishing a Spine Centre increase the lumbar MRI rate in comparison with other regions in Denmark.